Personal Taxpayer Compliance in Terms of Tax Rates, Understanding of Tax Regulations, and Quality of Service - Firmansyah Firmansyah; Meutia Layli (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The government maximizes tax revenue by carrying out tax reforms, namely changing the tax system from an official assessment system to a self-assessment. The purpose of the study is to determine taxpayer compliance in terms of tax rates, understanding tax regulations, and service quality. This research method is quantitative with primary data. Sampling in this study used purposive sampling. The data analysis technique of this study is multiple linear regression analysis with 72 respondents registered at KPP Pratama Samarinda. The results of the analysis of this study on tax rates have a positive effect on taxpayer compliance and can be interpreted by the government to be fair in determining the number of tax rates; understanding tax regulations has a positive effect on tax compliance, namely the better the level of understanding of taxpayer tax regulations will increase taxpayer compliance. The quality of service does not affect taxpayer compliance, and this is because tax is an obligation that can be imposed, and the current service system is technology-based.